BRICS Summits: A Discussion Club or Generator of Ideas of Social and Economic Development? - V. V. Perskaya; N. S. Revenko (Мир новой экономики, 2019)
The survey objective is to analyse the implementation of BRICS summits decisions and to identify emerging problems. It was carried out using the deductive method as well as the methods of comparative analysis, expert assessments, historical analogies. Support of the WTO, cooperation development in the areas of energy, transport, agriculture, environmental protection, culture, innovative processes stimulation, the global financial security strengthening are traditionally in the focus of summits’ attention. The new cooperation area is the enjoyment of opportunities associated with the use of information and communication technologies. However, the practice of implementing decisions taken is too bureaucratic, and the assessment of its effectiveness is formalised due to the lack of reliable business contacts between research teams, schools of thought or universities. Even with the allocation of funds for a specific task, it is difficult to find a team to complete it effectively. Therefore, even a clearly defined mechanism does not ensure the objective to be implemented, and consultations and meetings held at the working groups level are reduced to an exchange of views. It is essential to name in the BRICS documents specific organisations responsible for the implementation of decisions. It is advisable to advise national news agencies to enhance coverage of the BRICS partnership.